Linking landscape structure and land cover pattern at a regional level - Quinta-Nova, L.C. (2021)
The concept of land units refer to coherent spatial areas that are characterized by a certain degree of homogeneity concerning certain properties like geology, soils and climate. The Land use mosaic corresponds to a circumstantial layer that represents the present state of the landscape depicting the present factors of resource allocation. Nevertheless the stable potential layer is related with the stable characteristics of each site and allows the identification of use constraints or potentials. In this study we use a methodology based in the land unit concept in order to define a stable potential layer at a regional level. Therefore, 26 land units were delimited for the Beira Baixa region. Those units resulted from the combination of geomorphology, soil parent material and bioclimatic influence. For each land unit representative samples were characterized in terms of its land use mosaic attributes. For that purpose selected landscape metrics were calculated, quantifying the land use mosaic geometrical characteristics, namely: Shannon’s Diversity Index, Edge Density, Mean Patch Size and Number of Patches. The existing land use types were also quantified. Finally a cluster analysis was performed to define groups of samples representing the land units that have the similar land use mosaic types. The validation of the previously defined land units confirmed the reliability of the proposed methodology, with most of the land units strongly influencing the land use mosaic. This relationship is stronger in the land units that occupy a higher extension in the region, mainly soils rich or very rich in silica under the influence of a mesomediterranean subhumid bioclimate.